Expression of Human Mutant Preproinsulins Induced Unfolded Protein Response, Gadd45 Expression, JAK-STAT Activation, and Growth Inhibition in Drosophila - Tatsuki Yamazoe (MDPI AG, 2021)
Mutations in the insulin gene (INS) are frequently associated with human permanent neonatal diabetes mellitus. However, the mechanisms underlying the onset of this genetic disease is not sufficiently decoded. We induced expression of two types of human mutant INSs in Drosophila using its ectopic expression system and investigated the resultant responses in development. Expression of the wild-type preproinsulin in the insulin-producing cells (IPCs) throughout the larval stage led to a stimulation of the overall and wing growth. However, ectopic expression of human mutant preproinsulins, hINSC96Y and hINSLB15YB16delinsH, neither of which secreted from the β-cells, could not stimulate the Drosophila growth. Furthermore, neither of the mutant polypeptides induced caspase activation leading to apoptosis. Instead, they induced expression of several markers indicating the activation of unfolded protein response, such as ER stress-dependent Xbp1 mRNA splicing and ER chaperone induction. We newly found that the mutant polypeptides induced the expression of Growth arrest and DNA-damage-inducible 45 (Gadd45) in imaginal disc cells. ER stress induced by hINSC96Y also activated the JAK-STAT signaling, involved in inflammatory responses. Collectively, we speculate that the diabetes-like growth defects appeared as a consequence of the human mutant preproinsulin expression was involved in dysfunction of the IPCs, rather than apoptosis.